COX-2 and Ki-67 in Breast Cancer: A New Perspective on Tumor Pathology and Progression - Akanksha Hegde; Usha M; Rashmi K (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Breast cancer is a formidable health issue, necessitating continuous research for improved prognostic and therapeutic strategies. Cycloxygenase-2 (COX-2) is linked to aggressive breast cancers, characterized by high-grade tumors, large size, lymph node involvement, HER-2 overexpression, and ERnegativity. Ki-67, which is used to measure cell growth, is predictive of chemotherapy response in ER and PR-negative breast cancers. High Ki-67 is associated with elevated recurrence rate and poorer prognosis. This study evaluated COX-2 andKi-67 expression in breast carcinoma and their correlation with clinicopathological features. Elevated Ki-67 is linked to higher recurrence and poorer prognosis. Methods: This retrospective cross-sectional study included 70 cases of invasive breast carcinoma diagnosed between August 2022 and July 2024. Immunohistochemistry was performed on formalin-𿿿xed, paraf𿿿n-embedded tissue sample for COX-2 andKi-67. COX-2 expression was scored based on quantity and intensity, while Ki-67was scored using St. Gallen Consensus thresholds. Associations were analyzedusing Pearson’s Chi-square or Fisher’s exact test, with p<0.05 consideredsigni𿿿cant. Results: The study revealed signi𿿿cant associations between high expressionlevels of COX-2, Ki-67 with aggressive tumor characteristics, including lrger tumor size, advanced stage, lymphovascular invasion (LVI), perinodal spread ad /PR negativity (P -<0.001). Though no signi𿿿cant association was found wth e, SBR(Scarff-Bloom-Richardson) grade, N stage, perineural invasion(PNI) and Her2 status. Conclusion: High COX-2 and Ki-67 expression correlate with aggressive breast cancer features, supporting their role as prognostic markers and potential therapeutic targets, particularly in hormone receptor-negative and triple-negative subtypes.